Research Advances in Pharmacology, Safety, and Clinical Applications of Yunnan Baiyao, a Traditional Chinese Medicine Formula - Yao, Qi; Chang, Bo-tao; Chen, Rong; Wei, Yi-jing; Gong, Qiu-ju; Yu, Dan; Zhang, Yang; Han, Xu; Yang, Hong-bo; Tang, Song-jiang; Gao, Ying (Frontiers in Pharmacology, 2021)
Ethnopharmacology relevance: Yunnan Baiyao (YNBY), a traditional Chinese medicine formulae, has some significant properties including activating blood circulation to dissipate blood stasis (Huo-Xue-Hua-Yu), eliminating swelling and alleviating pain (Xiao-Zhong-Zhi-Tong), and eliminating necrotic tissues and promoting granulation (Qu-Fu-Sheng-Ji). Aim of this study: This paper intends to provide a comprehensive and critical analysis of studies on YNBY, proposing new possible therapeutic directions of this formulae. Materials and Methods: Relevant data on YNBY were retrieved from available databases and a hand-search by searching the keywords such as “Yunnan Baiyao”, “pharmacology”, “toxicity”, and “clinical applications”. Results: Traditionally, YNBY has been used to cure haemorrhage, bruises, swelling and pain caused by injuries in the Chinese folk. Modern pharmacological studies show that YNBY possesses pharmacological activities including hemostasis, invigorating the circulation of blood, wound healing, anti-inflammation, analgesia, antibiosis, infection prevention, and other effects. Toxicological studies demonstrate that YNBY has a certain toxicology, which is mainly caused by Aconitum alkaloids from Cao-wu (CW, Aconiti Kusnezoffii Radix). The developmental non-toxic reaction dose (NOAEL) of YNBY for embryos and fetuses is 0.5 g/kg in rats. In addition, the NOAEL for fertility and early embryo development toxicity is 4.0 g/kg in rats. Clinical trials have confirmed the safety of YNBY in a large number of patients, and adverse drug reactions (ADRs) such as abdominal pain, diarrhea, allergy, and others in very few people. YNBY is routinely used in clinic to cure bleeding, pain, swelling, upper digestive tract ulcer, postoperative wound, arthritis, mouth ulcers, ulcerative colitis, and etc. Conclusions: Hemostasis is a conspicuous effect of YNBY. Except for this effect, analgesia and anti-infection may be new research directions of this formulae. In addition, the in vitro and in vivo pharmacology, and mechanisms of action of YNBY are encouraged as well as the pharmacokinetics of this formulae. Furthermore, the material basis of the pharmacological effects of YNBY also needs clear identification.